PERANCANGAN SISTEM PENJUALAN AKSESORIS KUCING PADA TOKO PETSHOP ARSENAL JAMBI - Lisdarti - (JURNAL AKADEMIKA)
Development of computer technology is now very rapidly and many widely known. Masyarakatpun increasingly facilitated in obtaining the information. One of these technological advances are trading through a computer, and not a few people masi trade manually or computerized systems still do not know, by people or more in the know sytem written. To overcome these masala me as the author offers a solution by means of computerized data mengola to overcome existing masala on ARSENAL pet store. The purpose of this mengola computerized data easier for a person to transact the sale or purchase of data processing.